2015
DOI: 10.1364/oe.23.024236
|View full text |Cite
|
Sign up to set email alerts
|

Active radiation hardening of Tm-doped silica fiber based on pump bleaching

Abstract: Tm-doped fiber laser or amplifier can be applied in varied adverse environments. In this work, we demonstrate the pump bleaching of Tm-doped silica fiber with 793nm pump source under gamma-ray irradiation in the range 50Gy-675Gy. The recovery time, the fiber slope efficiency and the fiber cladding absorption spectra after irradiation and bleaching have been measured. It is found that the recovery time and radiation induce absorption are positively associated with doses, however, the fiber slope efficiency of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Besides, remarkable drop of the output power is observed with the increase of the radiation dosage. This phenomenon is consistent with the experiments reported for both Yb-doped fiber lasers and Tm-doped fiber lasers [34][35][36].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Besides, remarkable drop of the output power is observed with the increase of the radiation dosage. This phenomenon is consistent with the experiments reported for both Yb-doped fiber lasers and Tm-doped fiber lasers [34][35][36].…”
Section: Resultssupporting
confidence: 93%
“…For low power Er-doped and Er/Yb-codoped fiber amplifiers, experiments show that, without radiation-hardening or radiation-resistant treatment, a typical gain decrease over 50% at ∼100 Gy can be expected [32,33]. For moderate power Tm-doped fiber lasers, in 2015, Li reported the degradation of a 10 W level Tm-doped fiber laser with the Tm-doped fiber exposed to gamma radiation [34,35]. Experiments show that the output power and slope efficiency of the laser decrease monotonously with the accumulation of the radiation dose.…”
Section: Introductionmentioning
confidence: 99%
“…More generally, absorption spectra measurements on Tm 3+ -doped silica (67,77) and fluoride (74,78) fibers and on Yb 3+ -doped silica fiber (43,75,79,80) showed that broad absorptions in the Vis regions correlate directly with the onset of PD. This finding implies that light-induced color centers in the silica and fluoride fibers underlie PD, with the overlapping of the induced absorption and Ln emission bands explaining the luminescence decay in photodarkened materials.…”
Section: Photodarkening and Color Centersmentioning
confidence: 98%
“…As a consequence, most of the past studies were then devoted to RE-doped fiber characterization in order to identify the best fiber types to increase the tolerance of EDFA or EDFS first, and second to understand the basic mechanisms at the origin of the high radiation sensitivities of REDFs compared to telecom-grade passive optical fibers. Among the different types of RE-doped fibers, erbium (Er) and Er/ytterbium (Er/Yb)-doped fibers are the most studied [267][268][269][270][271], but other RE elements have also been considered in the past [92,272] or are today being investigated as promising technologies for future applications [273]. Characterizing the radiation response of REDFs appears to be more complex than the characterization of the transmission degradation of passive optical fibers.…”
Section: Rare-earth-doped Fibers Edfa and Edfsmentioning
confidence: 99%